Acoustic Characteristics of the Voice for Brazilian Portuguese Speakers Across the Life Span - Spazzapan, Evelyn Alves [UNESP]; Fabron, Eliana Maria Gradim [UNESP]; Berti, Larissa Cristina [UNESP]; Chagas, Eduardo Federighi Balsi; Marino, Viviane Cristina de Castro [UNESP] (Elsevier, 2020)
Introduction: Vocal changes occur across the life span and can be reflected in acoustic measurements. Objective: To investigate the characteristics of voice production of the Brazilian Portuguese speakers across the life span based on acoustic measures of Fundamental Frequency (fo) and noise-to-harmonic ratio (NHR) and to verify the differences in these measures between men and women. Methods: A total of 526 recordings from Brazilian Portuguese speakers aged 5–93 years were included. Voices from these speakers were judged with normal vocal quality for their age using the G parameter of the GRBAS scale. The recordings were divided into 12 age groups (5–7 years; 8–9; 10–11; 12; 13–15; 16–18; 19–29; 30–39; 40–49; 50–59; 60–69 and, 70–93 years old). Acoustic analysis was conducted, extracting the parameters fo and NHR through Multi-Dimensional Voice Programsoftware. Results: For women, there was a gradual decrease in fo from childhood to older age. Older women (60–93 years old) showed a lower fo than age groups up to 19–29 years (P< 0.00). For men, there was a decrease in fo up to the age group of 13–15 years (P< 0.00) and, then, it remained stable. Differences between sexes occurred from 12 years old, with higher fo values for women than men (P< 0.00). The NHR parameter remained stable across the life span for women while higher values for older subjects were found for men (P< 0.04). Regarding sex, men showed a higher NHR value than women (P< 0.002). Conclusion: Vocal changes occur across the life span and are reflected in the acoustic measure of fo for men and women. The beginning of vocal changes occurs from 12 years old with differences between sexes. The NHR measure was sensitive to indicate changes over a lifetime for men, with higher values for older subjects.
Keywords: Voice—Life span—Acoustic—Child—Adult—Aged